2021
DOI: 10.1002/nop2.852
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs towards implementation of nurse prescribing among general nurses and nurse specialists in China: A cross‐sectional survey study

Abstract: Prescriptive authority has been strictly in control within the realm of the medical profession for a long time (Fisher, 2010). However, prescriptive authority has become a reality amongst certain nurses in dozens of countries in response to growing demands for health care (Creedon et al., 2015;Delamaire & Lafortune, 2010). Nurse prescription has experienced a long process of development and was implemented at different times in different countries. It initially developed slowly, and was first introduced in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…In the opinion of the majority of respondents, this will improve the function-ing of the healthcare system, increase patients' access to health services, and increase the prestige of the profession. Similar benefits resulting from the extension of nurses' competencies are indicated by other studies in this area [19][20][21]. Furthermore, respondents believe that they are properly prepared and capable of independently providing the patient with advice within the scope provided by Polish legislation [22].…”
Section: Discussionsupporting
confidence: 55%
“…In the opinion of the majority of respondents, this will improve the function-ing of the healthcare system, increase patients' access to health services, and increase the prestige of the profession. Similar benefits resulting from the extension of nurses' competencies are indicated by other studies in this area [19][20][21]. Furthermore, respondents believe that they are properly prepared and capable of independently providing the patient with advice within the scope provided by Polish legislation [22].…”
Section: Discussionsupporting
confidence: 55%
“…In a cross-sectional study conducted on 928 participants with a bachelor's or master's degree and medical students in Warsaw, Poland, Zarzeka et al, the results showed a significant relationship between nurses' knowledge level and educational attainment and their positive attitude to taking the independent role of prescribing [17]. In the Ling et al study, the years of clinical work experience and education degree were positively correlated with nurses' attitudes and beliefs towards nurse prescribing [18].…”
Section: Discussionmentioning
confidence: 96%
“…The delegation of authority from physicians to nurses represents one of the most important elements in the professionalization process of nursing [ 18 ] and expanding nurses’ authority is a significant contributor to professional autonomy [ 19 ]. Various studies describe positive attitudes of physicians and nurses toward expanding nurses’ authority in several areas based on their belief that this will improve the quality of care [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%